ANALISIS KESALAHAN BERBAHASA ARAB TULIS PESERTA MUSABAQAH MAKALAH AL-QUR’AN TINGKAT PROVINSI SULAWESI TENGGARA TAHUN 2016 - Laode Abdul Wahab (Institut Agama Islam Negeri Kendari, 2018)
This research has been carried out to focus on the Errors Analysis of Arabic Writing for the participants of Musabaqah Makalah Al-Qur’an (MMQ) in the Southeast Sulawesi Province Level, in 2016. The data analyzed is 54 documents of Arabic Writing from the Participants of MMQ. The results indicate that all documents are indexed nothing is free from phonological, morphological, syntactic, and writing errors, consisting of a form of error of ziyadah (addition), naqis (subtraction), badal (replacement), hadzf (disappearance) and derivative error, although it is distributed differently based on every level of Arabic linguistics. The participants of MMQ competence contributed to the error. At the phonological level, the frequency of badal occurrence is very high, and at the morphological level the frequency of occurrence of derivative error is very high as well, while at the syntactic level, the frequency of occurrence of derivative error is high, as for at the all writings are categorized as derivative error type. The errors has caused the linguistic consequences to damage the structure of the alphabet, structure of the word, and structure of the sentence which leads to the destruction of the structure of the meaning. The errors are consequential on local error although it does not lead to misinterpretation and global error which will make the readers misinterpreted. In the process of Arabic writing, the verses from Holy Qur’an dan Hadith must be believed as a process of theophonological, theomorphological, theosyntactic and theosemantic of Arabic. This is intended as an effort by participants of MMQ to maintain the purity of Holy Qur’an.